Effects of active warm-up and diurnal increase in temperature on muscular power - Racinais, S.; Blonc, S.; Hue, O. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To investigate the effects of both an active warm-up (AWU) and the diurnal increase in body temperature on muscular power.